Depression and anxiety in acute ischemic stroke involving the anterior but not paramedian or inferolateral thalamus - Scharf, Anne-Carina; Gronewold, Janine; Eilers, Andres; Todica, Olga; Moenninghoff, Christoph; Doeppner, Thorsten R.; de Haan, Bianca; Bassetti, Claudio L.; Hermann, Dirk M. (Frontiers in Psychology, 2023)
Background and objectives Emotional and cognitive deficits are prevalent in strokes involving the thalamus. In contrast to cognitive deficits, emotional deficits have not been studied prospectively in isolated thalamic stroke. Methods In 37 ischemic thalamic stroke patients (57.0 [50.0; 69.5] years [median (Q1; Q3)], 21 males, 5 anterior, 12 paramedian, 20 inferolateral vascular territory), and 37 non-stroke control patients matched for age and sex, we prospectively examined depression, anxiety, activities of daily living, and quality of life at 1, 6, 12, and 24 months post-stroke using the Hospital-Anxiety-and-Depression Scale (HADS), Nürnberger-Alters-Alltagsaktivitäten scale (NAA), and Short Form-36 (SF36) questionnaire. Voxel-based lesion-symptom mapping (VLSM) and lesion-subtraction analyzes were performed to determine associations between questionnaire scores and thalamic stroke topography. Results At 1 month post-stroke, anterior thalamic stroke patients had higher depression scores [8.0 (7.5; 10.5)] than paramedian [4.5 (1.0; 5.8)] and inferolateral [4.0 (1.0; 7.0)] thalamic stroke patients. Furthermore, anterior thalamic stroke patients had higher anxiety scores [11.0 (8.0; 14.5)] than their matched controls [2.5 (2.0; 2.5)], paramedian [4.5 (1.0; 5.8)] and inferior [4.0 (1.0; 7.0)] thalamic stroke patients. Depression and anxiety scores in anterior thalamic stroke patients remained high across the follow-up [depression: 9.0 (3.5; 13,8); anxiety:10.05 (2.8, 14.5)]. Physical health assessed by SF36 was intact in anterior [1 month post-stroke: T-score = 55.9 (37.0; 57.6)] but reduced in inferolateral [44.5(32.4; 53.1)] thalamic stroke, whereas mental health was reduced in anterior thalamic stroke [32.0 (29.8; 47.3)]. VLSM confirmed that voxels in the anterior thalamus around Montreal Neurological Institute (MNI) coordinates X = −8, Y = −12, Z = 2 were more often affected by the stroke in depressed (HADS-score ≥ 8) than non-depressed (HADS-score < 8) patients and voxels around coordinates X = −10, Y = −12, Z = 2 were more often affected in anxious (HADS-score ≥ 8) than non-anxious (HADS-score < 8) patients. Conclusion Anterior, but not paramedian or inferolateral thalamic stroke was associated with depression and anxiety. Even though our results are mostly significant in the left thalamus, this observation on stroke laterality might be confounded by the fact that the right hemisphere was underrepresented in our study.